Overactive bladder after female genital mutilation/cutting (FGM/C) type III - Abdulcadir, Jasmine (BMJ Publishing Group, 2013)
A 27-year-old Somali woman with type III a–b female genital mutilation/cutting, consulted because of slow micturition, voiding efforts, urgency and urge incontinence (overactive bladder). She also referred primary dysmenorrhoea and superficial dyspareunia making complete sexual intercourses impossible. We treated her by defibulation and biofeedback re-educative therapy. We also offered a multidisciplinary counselling. At 5 months follow-up, urgency and urge incontinence had resolved and she became pregnant.